Growth of metal-metal oxide nanostructures on freestanding graphene paper for flexible biosensors. - Soo, Anna Jing Mei. (2012)
Flexible biosensors are of considerable current interest for the development of portable point-of-care medical products, minimally-invasive implantable devices, and compact diagnostic platforms. We report a new type of flexible electrochemical sensors fabricated by depositing high-density Pt nanoparticles on freestanding reduced graphene oxide paper (rGOP) carrying MnO2 nanowire networks. The triple-component design offers new possibilities to integrate the mechanical and electrical properties of rGOP, the large surface area of MnO2 networks, and the catalytic activity of well-dispersed and small-sized Pt nanoparticles prepared via ultrasonic-electrodeposition. The sensitivity and selectivity that the flexible electrode demonstrated for nonenzymatic detection of H2O2 has enabled its use for monitoring H2O2 secretion by live cells. We envision our strategy of structurally integrating of metal, metal oxide, and graphene paper would provide new insights on designing flexible electrodes for a wide range of applications in biosensing, bioelectronics, and lab-on-a-chip devices.